The Effect of Accuracy of Giving Diagnosis Codes on Diseases in the Verification of the Sosial Security Organizing Agency (BPJS) in PKU Muhammadiyah Sruweng Hospital - Novi Nugraheni Novi Nugraheni (Health Media, 2021)
The purpose of this study was to obtain an overview of the effect of the accuracy of the diagnosis code in cases of internal medicine on BPJS verification at PKU Muhammadiyah Sruweng Hospital in 2018. This research was carried out at PKU Muhammadiyah Sruweng Kebumen Hospital in Casemix Sub Section. This study uses descriptive method with a quantitative approach, samples taken by means of sample random sampling and using linear regression. Based on the results of the study and discussion of the accuracy of the provision of a diagnosis code in cases of internal disease as much as 59 (68.6%), while the inaccuracy of the provision of a diagnostic code in cases of internal disease was 27 (31.4%). Smooth verification of BPJS claims 54 (62.8%), while pending 32 (37.2%). While the results of a simple linear regression test the influence of the accuracy of the provision of diagnostic codes in cases of internal diseases against BPJS verification in PKU Muhammadiyah Sruweng Hospital obtained a significant value of 0,000. The significance value is <0.1, meaning that Ho is rejected and H1 is accepted so that there is an influence between the accuracy of giving a diagnostic code in cases of internal disease to BPJS verification.